Forensic Accounting and the Combating of Economic and Financial Crimes in Ghana - Evans O. N. D. Ocansey (European Scientific Journal, ESJ, 2017)
Economic and financial crimes have plagued every corner of the economies of the world. These crimes affect all firms and the economies of nations (developed, developing and under-developed). Continuous research confirmed a strong demand for the need of the prevention and detection of these crimes by institutions and nations. However, economic and financial crimes are difficult to detect and most of those detected are not reported for the fear of bad publicity and loss of investor confidence. Forensic accountants are perceived to have the training and skills needed to combat economic and financial crimes. Therefore, the research examined the relevance of forensic accounting technique application in the combating of these crimes in Ghana. The research employed survey research design by sampling all the technical officers (66) of Economic and Organized Crime Office of Ghana and data was analyzed through a regression model. It was found that, the application of forensic accounting technique has significant impact on the combating of economic and financial crimes in Ghana. Therefore, all institutions (anti-corruption agencies and companies) should establish forensic accounting unit to help strengthen internal controls and ensure thorough investigation in order to prevent, deter and detect financial and economic crimes. Moreover, Institute of Chartered Accountants-Ghana and National Accreditation Board of Ghana should ensure that forensic accounting courses are included in the academic and professional curricula of Ghana Universities and professional institutions to ensure the training and increase the awareness of forensic accounting in Ghana.